(untitled) (The Research of Medical Science Review, 2025)
Background: Pan brachial plexus injury is a devastating injury leading to permanent functional deficit and psychological scarring. The most common cause of traumatic adult pan-brachial plexus injury in motorbike accidents. The timing of presentation of these patients play a vital role in choosing the surgical intervention for the deficits. Other factors that determine the overall outcome of treatment include level and pattern of injury. Objective: To describe the various surgical techniques to restore the elbow flexion post pan brachial plexus injury according to the time of presentation, pattern and level of injury. Study design: Prospective observational study Place and duration of study: Combined Military Hospital, Lahore Pakistan, from 1 st -July-2022 to 31 st -july-2023. Methodology: After providing informed consent, a total of 26 patients with mean age of 29 years were included. Depending on when the injuries occurred, the study included a variety of surgical procedures, including as proximal explorations, distal nerve transfers and free functional muscle transfers. Results: The study's surgical procedures differed according to the period of the injury, with a mean participant age of 29 ± 7.14 years and a male preponderance (73.1%). Proximal exploration done in 8 patients, distal nerve transfers in 9 patients and functional muscle transfers in 9. Conclusion: When surgical interventions for elbow flexion restoration are timed according to the injury phase, patients with pan-brachial plexus injuries see significant increases in their muscular strength. The effectiveness of proximal exploration, distal nerve transfers, pedicled or functional muscle transfers cannot be over emphasized. These operations emphasize how important it is to use timely, appropriate surgical techniques that are tailored to the damage stage.